Temperature dependent thermoelectric properties of cuprous delafossite oxides. (1st January 2019) - Feng, Yining; Elquist, Aline; Zhang, Yuepeng; Gao, Kaizhong; Ferguson, Ian; Tzempelikos, Athanasios; Lu, Na
Abstract: The use of nanostructured delafossite oxides in thermoelectric (TE) applications has attracted a great interest due to their high performance and long-term stability at elevated temperatures. Cuprous delafossites, CuMO2 (M = Al, Cr, Fe, Ga, Mn), compared to conventional TE materials, such as Bi2 Te3, PbTe and SiGe, are non-toxic and more earth abundant. In particular, CuAlO2 compound shows a great potential for high performance thermoelectric materials. In this work, a systematic study of temperature dependent TE properties of cuprous delafossite materials, CuAlO2, is reported. The optimization of the TE properties has been realized by controlling nanostructure size around 80 nm CuAlO2 powder was prepared using a solid-state synthesis method at ∼1373 K in nitrogen/air atmosphere. The nanostructure size was controlled by a high energy ball milling process. Reducing the particle size of nanostructured bulk materials decouples interdependent electron and phonon transport and results in a lattice thermal conductivity decrease without deteriorating electrical conductivity. The high effective mass plays a dominant role in the high Seebeck coefficient and low electrical conductivity. The power factor reached ∼0.78 × 10 −5 W/mK 2 at 780 K. Temperature dependent TE properties, including Seebeck coefficient, electrical conductivity, and thermal conductivity are analyzed. The processing-structure-property correlation of these materials are discussed.